A Handbook for Entrepreneurs on Solid Waste Management A Step Towards Atmanirbhar Bharat. - Singh, Shyamli (Cambridge Scholars Publisher, 2022)
This book is a unique representation of the learning and experience in the area of waste management. It will work as a tool for students, young professionals and people who are passionate about building their career in the field of waste management in India. The book takes entrepreneurs through the journey of forming and working of enterprises/start-ups. It provides solutions to common concerns of entrepreneurs in the form of modules on subject matter of waste management, forming an enterprise, exploring opportunities, implementation and management of projects, and other important aspects invo.